2019
DOI: 10.1002/hep.30542
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Ductular Reaction by Stem Cell Derived Extracellular Vesicles in MDR2 Knockout Mice via Lethal‐7 microRNA

Abstract: Cholangiopathies are diseases that affect cholangiocytes, the cells lining the biliary tract. Liver stem cells (LSCs) are able to differentiate into all cells of the liver and possibly influence the surrounding liver tissue by secretion of signaling molecules. One way in which cells can interact is through secretion of extracellular vesicles (EVs), which are small membrane‐bound vesicles that contain proteins, microRNAs (miRNAs), and cytokines. We evaluated the contents of liver stem cell–derived EVs (LSCEVs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…EVs mediate inflammatory or fibrogenic responses in hepatic cells by delivering cargo mediators, which means that EVs could be used as therapeutic tools or drug carriers to regulate functions of cells by delivering mediators to maintain homeostasis during liver diseases . For example, EVs secreted from liver stem cells contained elevated levels of miRNA let‐7a, and injection of stem cell‐derived EVs ameliorated ductular reaction and liver fibrosis in Mdr2 −/− mice by delivering cargo let‐7a . Tunicamycin is a drug that causes hepatic ER stress followed by steatosis in mice and used as a drug‐induced NAFLD model.…”
Section: Therapeutic Potentials Of Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs mediate inflammatory or fibrogenic responses in hepatic cells by delivering cargo mediators, which means that EVs could be used as therapeutic tools or drug carriers to regulate functions of cells by delivering mediators to maintain homeostasis during liver diseases . For example, EVs secreted from liver stem cells contained elevated levels of miRNA let‐7a, and injection of stem cell‐derived EVs ameliorated ductular reaction and liver fibrosis in Mdr2 −/− mice by delivering cargo let‐7a . Tunicamycin is a drug that causes hepatic ER stress followed by steatosis in mice and used as a drug‐induced NAFLD model.…”
Section: Therapeutic Potentials Of Extracellular Vesiclesmentioning
confidence: 99%
“…106 For example, EVs secreted from liver stem cells contained elevated levels of miRNA let-7a, and injection of stem cell-derived EVs ameliorated ductular reaction and liver fibrosis in Mdr2 −/− mice by delivering cargo let-7a. 107 Tunicamycin is a drug that causes hepatic ER stress followed by steatosis in mice and used as a drug-induced NAFLD model. Rong et al isolated EVs secreted from cultured primary adipocytes harvested from mice treated with melatonin (20 mg/kg daily for 2 weeks, i.p.…”
Section: Associated Disease Modelmentioning
confidence: 99%
“…H19 deficient mice represented attenuated liver damage and fibrosis compared to wild-type mice after BDL, indicating the association of expression levels of H19 and liver conditions during cholestatic liver injury (18). Multidrug resistance 2 knockout (Mdr2 −/− ) mice are the most common transgenic mice that are utilized as the animal model of human PSC (19). Mdr2 −/− mice represent liver damage and fibrosis as well as elevated H19 expression in the liver, especially in female mice (20).…”
Section: H19mentioning
confidence: 99%
“…This means that EVs could be utilized as a drug or therapeutic mediator carrier to manage liver conditions. A recent study has demonstrated that injection of EVs isolated from liver stem cells attenuates ductular reaction and liver fibrosis in Mdr2 −/− mice via delivering cargo let-7, indicating the potentials of EVs as a therapeutic tool and an miRNA carrier (19). Injection of EVs carrying mediators, such as small molecules or nucleotides targeting lncRNAs could be performed to regulate lncRNA functions in vivo and manage liver conditions.…”
Section: Targeting or Utilization Of Evsmentioning
confidence: 99%
“…The miRNA, let‐7, belongs to a family of miRNAs required for development, growth, and metabolism regulation . A recent study demonstrated that dysregulation of let‐7 expression contributes to cholestatic liver diseases …”
mentioning
confidence: 99%